CRISPR/Cas genome editing for cotton precision breeding: mechanisms, advances, and prospects - Vijay Sheri; Harikrishnan Mohan; Phanikanth Jogam; Anshu Alok; Gulab Khan Rohela; Baohong Zhang (Journal of Cotton Research)
Abstract Cotton (Gossypium hirsutum L.) is one of the most important global crops that supports the textile industry and provides a living for millions of farmers. The constantly increasing demand needs a significant rise in cotton production. Genome editing technology, specifically with clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas) tools, has opened new possibilities for trait development in cotton. It allows precise and efficient manipulation within the cotton genome when compared with other genetic engineering tools. Current developments in CRISPR/Cas technology, including prime editing, base editing, and multiplexing editing, have expanded the scope of traits in cotton breeding that can be targeted. CRISPR/Cas genome editing has been employed to generate effectively CRISPRized cotton plants with enhanced agronomic traits, including fiber yield and quality, oil improvement, stress resistance, and enhanced nutrition. Here we summarized the various target genes within the cotton genome which have been successfully altered with CRISPR/Cas tools. However, some challenges remain, cotton is tetraploid genome having redundant gene sets and homologs making challenges for genome editing. To ensure specificity and avoiding off-target effects, we need to optimize various parameters such as target site, guide RNA design, and choosing right Cas variants. We outline the future prospects of CRISPR/Cas in cotton breeding, suggesting areas for further research and innovation. A combination of speed breeding and CRISPR/Cas might be useful for fastening trait development in cotton. The potentials to create customized cotton cultivars with enhanced traits to meet the higher demands for the agriculture and textile industry.